Expansion of fluvial transport of commodities through the Pantanal floodplains of Brazil: Potential impacts and interference by climate change - Pierre Girard; Fabio deOliveira Roque; Wilson Cabral de Sousa Jr; Stephen K. Hamilton (Conservation Science and Practice, 2025)
Abstract Inland waterways have historically been viewed as a desirable means for transporting commodities. However, creating and maintaining navigable river channels can entail substantial geomorphological modifications, resulting in changes to the ecohydrology of a river and its adjacent floodplains. In addition, barge traffic has important environmental impacts. The proposed expansion of the Paraguay River Hidrovia through the Pantanal floodplains of Brazil will negatively impact biodiversity due to bank erosion, water pollution, and the introduction of invasive species. Dredging would decrease the area and duration of inundation of connected floodplains renowned for their biodiversity, including fish and wildlife. Furthermore, the effects of the Hidrovia on greenhouse gas emissions are potentially important, although the net effects are complex and require further research. Global climate change is projected to cause greater variability in rainfall and river levels, with longer and more severe low water periods that would impede navigability and require further channel modifications. Modifications of the Paraguay River channel that lower the water levels and reduce the extent of surface water persisting during the dry season would negatively impact aquatic life in the main channel as well as in the floodplains, where recent increases in wildfire severity and excessive heat are already stressors. These changes threaten traditional livelihoods for people in the Pantanal, including artisanal fisheries, cattle ranching, and ecotourism.